Fragmentation of Identity in Mohsen Al-Ramli’s Novels (Fingers Pass) by Mohsen Al-Ramli - Ali, Doaa Kadhim (Journal of Posthumanism, 2025)
This research addresses the fragmentation of identity in the novel "Pass Fingers" by Iraqi author Mohsen Al-Ramli, as one of the most prominent themes reflecting the social, political, and cultural transformations experienced by Iraq, especially after 2003.The research is divided into:An introduction that covers the author’s biography, milestones in his life, and literary output. The first section defines the concept of "fragmentation" linguistically and technically, linking it to the political and social transformations experienced by Iraq, particularly the sectarian and ethnic divisions and multiple affiliations after the fall of the former regime. The second section presents the practical manifestations of this fragmentation in the novel through an analysis of several scenes and narrative texts, which reflect the division between original identity (Iraqi/rural) and acquired identity (Spanish/immigrant).Key Findings:Identity in "Pass Fingers" is not fixed, but rather torn between two realities: one is an Eastern past marked by oppression and harsh traditions, and the other is an open Western one that harbors an internal sense of alienation. In the narrative, his attachment to his identity is reflected in the author’s use of the original technique of "recall," despite his attempts to adapt to the new one. Identity in the novel experiences a state of sharp division as a result of alienation and nostalgia on the one hand, and rejection and new belonging on the other. The fragmented identity here represents an internal conflict within the narrator between belonging to the land and culture of childhood and his attempt to integrate into a Western society with different values. This reflects the crisis of postmodern man in a political and social context.